Assessing land use change from food croplands to rubber in Ghana's Ellembelle district: Implications for food self-sufficiency - George Ashiagbor; Victor Quarshie; Sandra Sawdiatu Inusah; Isaac Stanisluv Essah; Sinka Khadijah Abubakar; Erasmus Narteh Tetteh; Winston Adams Asante (Scientific African)
There is evidence that cocoa and cashew farmers are targeting croplands for expansion, reducing cropland areas with negative implications for food self-sufficiency in Ghana. However, research on the dynamics of rubber expansion and its possible impact on food self-sufficiency is limited. This study analysed the intensity of land use transition from food crops to rubber and its implications for food self-sufficiency among rubber-growing households in the Ellembelle District. Land use maps were used to analyse the intensity of transition associated with rubber and food crops from 1991 to 2022. Additionally, questionnaires were used to gather information on rubber expansion, cropland loss, and food self-sufficiency from 160 rubber farmers. A Chi-square test was used to determine the relationship between households that converted croplands to rubber and food self-sufficiency. The study showed that rubber had expanded by 9647.5 ha, mainly targeting food croplands. Majority (75.3 %) of farmers reported a decline in food availability, 68.5 % reported reduced access to food, and 49.3 % indicated a decline in dietary diversity, indicating a general decrease in food self-sufficiency. However, there was no statistically significant relation between farmers who converted cropland to rubber and food self-sufficiency. This suggests that the decline in food self-sufficiency is not a result of rubber expansion but of the disproportional cropland expansion to population growth and known challenges to crop production. To achieve food self-sufficiency, there is a need to increase food crop farming among rubber-growing farmers. This can be achieved by allowing rubber farmers to spare lands solely for food crop farming, providing subsidised agricultural inputs, and enhanced extension support. Also, creating a reliable market for staple food crops such as cassava and addressing supply chain obstacles like poor road networks are essential for making food crop farming competitive.